2013
DOI: 10.1149/05303.0097ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) A Brief Review of Doping Issues in III-V Semiconductors

Abstract: A brief review of n-type doping of GaAs, InGaAs and InP using ion implantation is presented. While the diffusion of the amphoteric dopant Si is not a significant issue its activation is limited to around 1×1019/cm3. This has prompted many studies into factors that might affect dopant activation including co-implantation to force site selection, damage and amorphization effects, elevated temperature implants and capping effects. A summary of these results is discussed. With interest in using III-V materials f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…According to Kevin S. Jones group research, it demonstrated that elevating implantation temperature could help destroyed lattices with recovery to avoid amorphous layers [4,5,9]. Prior to annealing, 15nm protective layer Al 2 O 3 was deposited by ALD to prevent surface degradation, and the previous literature has proved that using Al 2 O 3 for capping layer could prevent surface degradation due to group V easily loss [6,7]. After capping Al 2 O 3 on In 0.53 Ga 0.47 As, they were annealed by MWA 1P(0.6kW)-4P(2.4kW) for 100 s and by RTA 450-750°C for 8 s, respectively.…”
Section: Experimental Schemementioning
confidence: 99%
“…According to Kevin S. Jones group research, it demonstrated that elevating implantation temperature could help destroyed lattices with recovery to avoid amorphous layers [4,5,9]. Prior to annealing, 15nm protective layer Al 2 O 3 was deposited by ALD to prevent surface degradation, and the previous literature has proved that using Al 2 O 3 for capping layer could prevent surface degradation due to group V easily loss [6,7]. After capping Al 2 O 3 on In 0.53 Ga 0.47 As, they were annealed by MWA 1P(0.6kW)-4P(2.4kW) for 100 s and by RTA 450-750°C for 8 s, respectively.…”
Section: Experimental Schemementioning
confidence: 99%
“…Sub-15 nm ALD films of Al 2 O 3 have been shown to provide adequate surface protection at high annealing temperatures and have good etchant selectivity. [28][29][30] The complications associated with implantation and annealing of group III-As are not intractable, but the extra steps and difficulties associated with annealing may make growth doping more attractive in these materials.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (5) Q12mentioning
confidence: 99%
“…Indeed, silicon implantation has historically been used for III-V MOSFET implementation, but this technique suffers from two main disadvantages: (1) the surface and the crystal are damaged during the implantation, and (2) the doping level is limited to 1 × 10 19 atoms/cm 3 due to the amphoteric behavior of silicon [11]. For these reasons, two other unconventional solutions have been explored to further improve source/drain characteristics: (1) sulfur monolayer doping, which was successfully combined with Mo contacts to overcome the crystal damage induced by the implantation [12].…”
Section: Introductionmentioning
confidence: 99%